THE IMPLEMENTATION OF WRITERS WORKSHOP AS A PROCESS WRITING TO ENHANCE STUDENTS WRITING ABILITIES AND VOCABULARY LEARNING IN A KINDERGARTEN SETTING - Arbali, Julieta A. (2014)
This thesis is an exploratory case study concerning the impact of the implementation of writer's workshop as an early literacy activity on students' writing abilities and vocabulary learning in a kindergarten setting in South Jakarta, Indonesia. The study explores the implementation of mini lessons or the basic principles of process writing, teachers, and students' interaction, students' and peers' interactions in contributing to students' writing abilities and vocabulary learning. The study employs a qualitative research design method by using documents analysis as the principal instrument. Other sources such as transcripts from conversations and students' drawings are analyzed to strengthen the data. Subsequently,data from eleven kindergarten-2 students' writings are analyzed by using the concept of social constructivist theory for earl childhood learning (Dyson, 1999, 2006, 2010) and TEYL in Indonesia (Musthafa, 2010). The study reveals students' dependence on their phonemic awareness resulted in numerous incorrect written orthographies of English words in their writings. The implementation of writer's workshop allows teachers to integrate activities such as storytelling, field trip, wordlist and references to assist students in developing their vocabulary in their writing. Therefore, from the findings, it can be concluded that writer's workshop benefits students' writing abilities and vocabulary learning. Thus, it is recommended that writer's workshop be taught at a kindergarten level.;---